Síntese de catalisadores nanoporosos na ausência total e parcial de direcionadores orgânicos para pirólise catalítica de óleos pesados e intermediários - Costa, Maria José Fonseca (2013)
The processing of heavy oil produced in Brazil is an emergency action and a strategic plan to obtain self-sufficiency and economic surpluses. Seen in these terms, it is indispensable to invest in research to obtain new catalysts for obtaining light fraction of hydrocarbons from heavy fractions of petroleum. This dissertation for the degree of Doctor of Philosophy reports the materials preparation that combine the high catalytic activity of zeolites with the greater accessibility of the mesoporosity, more particularly the HZSM-5/MCM-41 hybrid, done by synthesis processes with less environmental impact than conventional ones. Innovative methodologies were developed for the synthesis of micro-mesoporous hybrid material by dual templating mechanism and from crystalline zeolitic aluminosilicate in the absence of organic template. The synthesis of hybrid with pore bimodal distribution took place from one-single organic directing agent aimed to eliminate the use of organic templates, acids of any kind or organic solvents like templating agent of crystalline zeolitic aluminosilicate together with temperature-programmed microwave-assisted, making the experimental procedures of preparation most practical and easy, with good reproducibility and low cost. The study about crystalline zeolitic aluminosilicate in the absence of organic template, especially MFI type, is based on use of H2O and Na+ cation playing a structural directing role in place of an organic template. Advanced characterization techniques such as X-Ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM), Highresolution Transmission Electron Microscopy (HRTEM), Adsorption of N2 and CO2, kinetic studies by Thermogravimetric Analysis (TGA) and Pyrolysis coupled to Gas Chromatography/Mass Spectrometry (Pyrolysis-GC/MS) were employed in order to evaluate the synthesized materials. Achieve the proposed objectives, has made available a set of new methodologies for the synthesis of zeolite and hybrid micro-mesoporous material, these suitable for catalytic pyrolysis of heavy oils aimed at producing light fraction